ChemInform Abstract: Ligand Bite Angle‐Dependent Palladium‐Catalyzed Cyclization of Propargylic Carbonates to 2‐Alkynyl Azacycles or Cyclic Dienamides. Issue 31 (5th August 2014) - Daniels, David S. B.; Jones, Alison S.; Thompson, Amber L.; Paton, Robert S.; Anderson, Edward A.
Abstract The cyclization products are obtained as inseparable mixtures.